Efficient robust private set intersection. (1st January 2012) - Dachman-Soled, Dana; Malkin, Tal; Raykova, Mariana; Yung, Moti
Computing set intersection privately and efficiently between two mutually mistrusting parties is an important basic procedure in the area of private data mining. Assuring robustness, namely, coping with potentially arbitrarily misbehaving (i.e., malicious) parties, while retaining protocol efficiency (rather than employing costly generic techniques) is an open problem. In this work, the first solution to this problem is presented.